Massive neonatal intracranial hemorrhage caused by bromadiolone: A case report. Issue 45 (November 2017) - Ma, Mingsheng; Zhang, Mengqi; Tang, Xiaoyan; Li, Zhenghong
Abstract: Rationale: Bromadiolone, often called a super-warfarin, is a potent rodenticide with long half-life. Skin and mucosal bleeding is the most common clinical manifestations of its intoxication. Bromadiolone intoxications in adults and children have been reported, but this phenomenon is rarely seen in fetuses. This paper presents a case of neonate with massive intracranial hemorrhage mediated by bromadiolone intoxication, highlighting that the bromadiolone is potentially lethal to the fetus. Patient Concerns: The male neonate presented with poor respiratory effort, decreased muscle tone, and pallor at birth. He developed generalized seizures on day 1 of life. His mother suffered from bleeding of oral mucosa and the subsequent lab screening for toxicants showed a bromadiolone level of 126 ng/mL. Diagnoses: Laboratory tests revealed that prolonged prothrombin time (PT) and activated partial thromboplastin time (aPTT). A computed tomography (CT) of his head revealed a severe subdural hematoma, which lead to midline shift, bilateral intraventricular hemorrhage, and subarachnoid hemorrhage. Serum from cord blood was collected and screened for toxicants. The result returned with a bromadiolone level of 94 ng/mL. Interventions: The neonate was treated with vitamin K, fresh-frozen plasma, and red blood cells. Outcomes: His parents required termination of all treatments, and the neonate unfortunately died shortly after. Lessons: Through clinical experience from this case, we believe that bromadiolone can be passed down to the fetus via placenta. Neonatal intracranial hemorrhage caused by bromadiolone is rare but potentially lethal. Pregnant women should be informed of the serious side effects of bromadiolone and this poisonous reagent should be avoided in any period during pregnancy.